Social change and the rising of deviance in the UAE society: An analytical study - Hared, Khadija; AlHourani, Mohammed (Al-Adab Journal, 2024)
The study addressed the social change and the rise of deviance in the UAE society, because the occurrence of deviance is one of the negative phenomena in society, especially if this deviance is towards children, which will result many problems that negatively affect society and undermine its security and safety. Therefore, the study aimed to explain and analyze the social changes and the rise of deviance in the UAE society, by identifying the changes occurring in the public sphere of society and their repercussions on family structure and their impact on family functions, which greatly influenced the emergence of deviance, and the factors that also emerged from these changes culturally and socially that contributed to the escalation of deviance, in addition to analyzing the role of public control policies in preventing deviance. This study is an analytical study.The study concluded that the social changes that permeated the family and the larger society and the changes happening in various general, cultural, social, and economic fields, had a significant impact on the escalation of children’s delinquency in UAE society. The study also emphasized the role of the state in establishing rehabilitation centers for delinquents, and the necessity of making changes in the goals of Some general policies pursued by some institutions that uses punishment only and emerging it with appropriate rehabilitative and correctional programs to prevent deviance.